No 'free ride' for African women: A comparison of head-loading versus back-loading among Xhosa women - Ray Lloyd; Bridget Parr; Simeon Davies; Carlton Cooke (South African Journal of Science)
Although contrasting evidence exists in the literature as to the economy of head-loading, there is a notion that head-loading is an extremely economical method of load carriage. This has become known as the 'free ride' hypothesis and, although untested, it is widely accepted. The purpose of this study was to test the 'free ride' hypothesis for head-load carriage among African women by comparing the relative economy of head-loading and back-loading. Twenty-four Xhosa women walked on a level treadmill, attempting to carry loads of between 10% and 70% of their body mass (BM) using both a backpack and a head basket. All 24 women carried at least 25% of their BM in both conditions. The relative economy of load carriage was calculated for loads of 10% to 25% of BM. Results indicated that the 'free ride' was not a generalisable phenomenon, with both methods realising economy scores close to unity (1.04 Â± 0.19 and 0.97 Â± 0.15 for head-loading and back-loading, respectively). The results did, however, reveal significant individual differences in economy scores and it is suggested that analysis of such individual differences in future may well be instructive in understanding mechanisms associated with greater economy in load carriage.